Virtual Fencing Is Comparable to Electric Tape Fencing for Cattle Behavior and Welfare - Campbell, Dana L. M.; Lea, Jim M.; Keshavarzi, Hamideh; Lee, Caroline (Frontiers in Veterinary Science, 2019)
Virtual fencing technology restricts animal movement via communicated signals without physical boundaries. Specifically, the eShepherdTM automated virtual fencing system operates via GPS technology and provides stimuli via a neckband device. An audio warning tone is emitted at the virtual boundary which is followed by an electrical pulse if the animal continues moving forward. Animal welfare is a priority consideration for the commercial implementation of virtual fencing systems. The current study assessed the effects of a virtual fence, in comparison to an electric tape fence, to contain eight groups of eight 12-14-month old steers within a six-hectare area across eight separate paddocks for four weeks following one week acclimation to the paddocks. Cattle were assessed across two cohorts (four groups/cohort) from January until March 2019 in Australia. Body weight and fecal samples from each animal were taken weekly. Fecal samples were processed for fecal cortisol metabolite (FCM) concentrations. IceQube R®’s fitted to the leg measured individual lying and standing time and the virtual fencing neckbands recorded GPS location and all administered audio and electrical stimuli. Cattle were maintained within their allocated area by both fence types across the four-week period and those with the virtual fences were responding correctly to the audio cue with an average of 71.51 ± 2.26% of all cues across all animals being audio only. There was individual variation in rate of learning. The electric tape groups in cohort 1 showed a greater increase in body weight over four weeks than the virtual fence groups (P = 0.006) but this difference was not confirmed in cohort 2. The fence type statistically influenced the total daily lying time (P = 0.02) with less lying in cattle from the virtual fence groups but this difference equated to an average of less than 20 minutes per day. There were no differences between fence types in FCM concentrations (P = 0.39) and the concentrations decreased across time for all cattle (P < 0.001). These results indicate that virtual fencing technology effectively contains animals in a prescribed area across four weeks without substantial behavioural and welfare impacts on the cattle.